(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. Complexity and multistage of wine technology increase risks of wine contamination by metal ions. That is why development of reliable, fast and cheap methods of toxic metals determination is actual task. The atomic absorption method possesses all above benefits; however, its sensitivity is not high enough. So, for the heave metals determination in wines on the level of maximum permissible concentration requires additional preconcentration at the probe pretreatment stage. The purpose of present work is the development of the procedure of atomic absorption determination of copper, cadmium, nickel and lead in wines through their selective preconcentration of silicas with chemically grafted iminodiacetic acid groups (SiO2-IDA) and ethylenediaminetriacetic acid (SiO2-EDTA) Methods. Sorption characteristics of chemically modified silicas for Cu (II), Cd (II), Ni (II) and Pb (II) were studied in dynamic mode, equilibrium concentrations of metal ions were determined by atomic adsorption. Results. Optimal conditions of Cu (II), Cd (II), Ni (II) and Pb (II) sorption were studied. Sorption – atomic absorption procedure of these metals quantification in aqueous solutions, was proposed. This procedure if suitable for analysis of red and white wines with satisfactory accuracy and reproducibility. Conclusions. The SiO2-IDA adsorbent appeared low efficient for metals preconcentration in dynamic conditions. The quantitative extraction of all Cu (II), Cd (II), Ni (II) and Pb (II) on SiO2-EDTA takes place at the pH = 4 – 5, while their quantitative elution can be achieved by adsorbent treatment with 1% Thio in 0.1 mol/l HCl. The optimal volume of the eluate is 2 ml for 0.1 g of adsorbent. Proposed approach was successfully applied for preconcentration and following atomic absorption determination of metal ions in red and white wines samples.